Brands Explore Human Relationships for Consumer Engagement : A Critical Analysis of Television Advertising in India - Trehan, Kulveen; Gupta, Aastha (Indian Journal of Marketing, 2015)
Within the critical codes of advertising executions, human relations (personal and social) in television ads were examined to know the recurring relationship projections in the present day Indian advertising. It was found that the individuals’ relationship with self is emerging as a preferred one, with romantic love and family relations often used either as site or subject to position the brand as integral, at times intimate, and more often, identifiable in the product category. Evidence pointed out at the homogenization of product-consumer relation as well as existing character- character and character - consumer relations across durables, non-durables, or other identified sponsors. From the purposive sample, it was noted that television ads used collectivistic appeals to use or create moments in life driven by the need to love and belong. Products are seldom directly talked at us but are artfully woven in relationship slices in seamless communication and persuasion.